Design Of A Web-Based Inventory System At PT. Anugerah Agro Palm Perkasa - Putra Panjaitan, Boby; Fitriani, Wirda; Andhika Putri, Nadya (Cattleya Darmaya Fortuna, 2025)
PT Anugerah Agro Sawit Perkasa is a company engaged in oil palm plantation and processing that has a high need for accurate and efficient inventory management. However, the inventory recording system that is still done manually or through spreadsheets causes various problems, such as stock data mismatches, potential human errors, and limitations in real-time reporting and stock monitoring. This research aims to design and develop a web-based inventory information system by utilising Dart, Flutter, and Pocketbase technologies. The methodology used is a mixed-method approach that combines quantitative analysis of data accuracy and qualitative analysis through interviews with logistics staff. System development was carried out using an iterative approach, starting from needs analysis, system design using UML, interface and backend implementation, to testing using black-box testing. The final result of this research is a web-based inventory system that can record and monitor incoming and outgoing goods transactions, present stock and transaction reports, and support decision making quickly and accurately. Evaluation of the system shows an increase in efficiency and accuracy of inventory data, while reducing manual workload in the company's operational environment.